2016
DOI: 10.1210/en.2015-1617
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Effects of Chronic Hyperandrogenemia in a New Model of Postmenopausal Polycystic Ovary Syndrome

Abstract: Postmenopausal women who have had polycystic ovary syndrome (PCOS) and chronic hyperandrogenemia may be at a greater risk for cardiovascular disease than normoandrogenemic postmenopausal women. The cardiometabolic effect of chronic hyperandrogenemia in women with PCOS after menopause is unclear. The present study was performed to test the hypothesis that chronic hyperandrogenemia in aging female rats would have more deleterious effects on metabolic function, blood pressure, and renal function than in normoandr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
1
31
0
2
Order By: Relevance
“…Monthly body weight and food intake were measured for 6 months after DHT withdrawal. At 13 months of age, body composition of ex-DHT and control rats (n = 10/group), including total body fat mass, total body lean mass, and total body water, were measured (4 in1 900 model Body Composition Analyzer; Echo-MRI, Houston, TX) according to the manufacturer’s instructions, as we previously reported [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Monthly body weight and food intake were measured for 6 months after DHT withdrawal. At 13 months of age, body composition of ex-DHT and control rats (n = 10/group), including total body fat mass, total body lean mass, and total body water, were measured (4 in1 900 model Body Composition Analyzer; Echo-MRI, Houston, TX) according to the manufacturer’s instructions, as we previously reported [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“… 11 Androgen excess is a key driver of increased cardiovascular risk. 12 , 13 , 14 , 15 , 16 , 17 We hypothesized that patients with IIH may have an increased risk of cardiometabolic disease compared with a cohort matched for obesity (BMI), age, and sex. The aim of this study was to define cardiometabolic risk in IIH, independent of BMI, and to identify trends in prevalence and incidence.…”
Section: Introductionmentioning
confidence: 99%
“…An important issue is that, after menopause, PCOS women still have elevated androgen levels (144, 145), which in turn may have some negative impact in favoring metabolic alterations and, possibly, an increased cardiovascular (CV) risk. Preliminary data from a new rat model of postmenopausal PCOS have in fact shown that they are characterized by higher insulin and non-fasted glucose levels than aged controls (146).…”
Section: Dhea and Fertilitymentioning
confidence: 99%